STUDI LITERATUR: PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Aska Fuadiyah, Laila; Suntari, Yustia; Dallion, Engga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of the Project Based Learning (PjBL) learning model on students' creative thinking abilities. The research method used is literature review. The data obtained is collected, analyzed and concluded to obtain conclusions regarding the literature study. Data collection techniques are obtained through notes and previous research, in the form of books, scientific reports, journals. The research results show that the learning model used greatly influences student development. The reason why students are less able to have creative thinking skills is because the learning model used by teachers when teaching is too monotonous so that students are bored and less motivated in learning. The proposed solution to overcome this is to use an interactive and interesting learning model, one of which is using the Project Based Learning (PjBL) model. Using the Project Based Learning (PjBL) model makes students more motivated to learn to make projects, makes students more creative and innovative, able to solve problems, and able to increase collaboration between students.